2022
DOI: 10.1007/s40120-022-00351-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Carbidopa–Levodopa Enteral Suspension and Deep Brain Stimulation on Parkinson’s Disease-Related Pill Burden Reduction in Advanced Parkinson’s Disease: A Retrospective Real-World Cohort Study

Abstract: Introduction In advanced Parkinson’s disease (PD), a high pill burden is associated with poor compliance, reduced control of symptoms, and decreased quality of life. We assessed the impact of carbidopa–levodopa enteral suspension (CLES) and deep brain stimulation (DBS) on PD-related pill burden. Methods A retrospective cohort analysis was conducted in the IBM MarketScan and Medicare Supplemental databases. Patients with advanced PD, taking only PD medications, and initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…A retrospective cohort analysis has compared LCIG infusion (34 patients) with DBS (97 patients). 26 After 12 months of treatment, a significantly greater reduction in daily pill burden (p ≤ 0.0001), with more patients being able to discontinue oral medication completely, was observed in the LCIG infusion-treated group. Currently, LCIG and DBS are also being compared in the INfusion VErsus STimulation in Parkinson’s Disease (INVEST; NCT02480803) study in patients with PD.…”
Section: Infusion Therapies and Quality Of Life In Pdmentioning
confidence: 87%
See 1 more Smart Citation
“…A retrospective cohort analysis has compared LCIG infusion (34 patients) with DBS (97 patients). 26 After 12 months of treatment, a significantly greater reduction in daily pill burden (p ≤ 0.0001), with more patients being able to discontinue oral medication completely, was observed in the LCIG infusion-treated group. Currently, LCIG and DBS are also being compared in the INfusion VErsus STimulation in Parkinson’s Disease (INVEST; NCT02480803) study in patients with PD.…”
Section: Infusion Therapies and Quality Of Life In Pdmentioning
confidence: 87%
“…In advanced PD, a high pill burden is often associated with poor compliance, a progressively worsening control of motor and non-motor symptoms, and deterioration of QoL. 26 Indeed, studies have shown that up to 67% of Parkinson’s patients take <80% of their prescribed PD medications. 27 As PD progresses, further medication adjustments become necessary in order to adequately manage symptoms.…”
Section: Progressing From Oral Therapy To a Device-aided Therapymentioning
confidence: 99%
“…The link between sleep dysfunction and dopamine pathophysiology can also be supported by reduced binding of 11 C-raclopride in the hypothalamus among PD patients, which is a key sleep and autonomic regulatory center [ 38 ]. Switching to LCIG would allow reduction in other anti-parkinsonian medications and potentially achieving monotherapy during the day [ 39 ]. As result, reduction in other dopaminergic medications may lead to improvements in other non-motor symptoms such as insomnia, sedation and urinary urgency [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are limited real-world studies directly assessing and comparing the impact of CLES versus DBS on oral PD-related pill burden and resultant LEDD. A prior study of commercial and supplemental Medicare insured patients showed benefit of these device-aided therapies to reduce oral pill burden [ 22 ]. We extend these findings to include assessment of LEDD and focus this work on the 100% Medicare fee-for-service (FFS) population, as PD predominately affects older adults.…”
Section: Introductionmentioning
confidence: 99%